ASSESSING THE ROLE OF ISLAMIC LEADERSHIP AND WORK MOTIVATION ON EMPLOYEE ENGAGEMENT, MEDIATED BY JOB SATISFACTION - Lila Bismala; Syaifuddin Syaifuddin; Rasmulia Sembiring (Proceeding International Seminar of Islamic Studies, 2022)
Employee engagement is very important for organizations, and SMEs are no exception, so it is necessary to investigate what factors can affect employee engagement, either directly or indirectly. With a sample of 138 employees working in Muslim-owned SMEs, the researcher uses path analysis to examine the mediating effect of job satisfaction on the relationship between Islamic leadership and work motivation on employee engagement. Using the SPSS program, the results showed that the direct influence of Islamic leadership and work motivation on employee engagement was greater than the mediating effect of job satisfaction. The research results are useful for SMEs leaders in implementing Islamic leadership and increasing employee motivation.Keywords: Islamic leadership, work motivation, job satisfaction, employee engagement